Standardization of irrigation requirement of cowpea under naturally ventilaed poly house - ARUNYA S. KUMAR; Athulya T. K; Sahla N; Dr. Abdul Hakkim V. M (Guide) (Tavanur 2015 Department of Land and Water Resource and Conservation Engineering)
the present study was undertaken with the objective to determine the effect of different irrigation levels of yield of cowpea under naturally ventilated poly house. it was conducted at the experimental plot of PFDC farm, KCAET, Tavanur.
Standardization of irrigation requirement of cowpea under naturally ventilaed poly house